The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1063/5.0165029
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric artificial synapses for high-performance neuromorphic computing: Status, prospects, and challenges

Le Zhao,
Hong Fang,
Jie Wang
et al.

Abstract: Neuromorphic computing provides alternative hardware architectures with high computational efficiencies and low energy consumption by simulating the working principles of the brain with artificial neurons and synapses as building blocks. This process helps overcome the insurmountable speed barrier and high power consumption from conventional von Neumann computer architectures. Among the emerging neuromorphic electronic devices, ferroelectric-based artificial synapses have attracted extensive interest for their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…In addition to the aforementioned insights, optimizing vacuum-based devices and electronic systems using bio-inspired optimization approaches (e.g., Ant Colony Optimization (ACO), Genetic Algorithms (GA), Particle Swarm Optimization (PSO), Simulated Annealing (SA)) holds considerable promise [66,67]. Since the vacuum gate dielectric degrades the coupling capacitance, leading to worse carrier control, leveraging negative capacitance ferroelectric materials [68][69][70] to improve such carbon nanodevices can be a Simulation of such devices and their derivatives (considering different gate configurations) while taking into account scattering mechanisms within the NEGF framework can provide a deeper insight into the behavior and performance projection of carbon-based nanotransistors in radiative environments. Additionally, exploring the analog/RF performance of these devices presents an intriguing avenue for further investigation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the aforementioned insights, optimizing vacuum-based devices and electronic systems using bio-inspired optimization approaches (e.g., Ant Colony Optimization (ACO), Genetic Algorithms (GA), Particle Swarm Optimization (PSO), Simulated Annealing (SA)) holds considerable promise [66,67]. Since the vacuum gate dielectric degrades the coupling capacitance, leading to worse carrier control, leveraging negative capacitance ferroelectric materials [68][69][70] to improve such carbon nanodevices can be a Simulation of such devices and their derivatives (considering different gate configurations) while taking into account scattering mechanisms within the NEGF framework can provide a deeper insight into the behavior and performance projection of carbon-based nanotransistors in radiative environments. Additionally, exploring the analog/RF performance of these devices presents an intriguing avenue for further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the aforementioned insights, optimizing vacuum-based devices and electronic systems using bio-inspired optimization approaches (e.g., Ant Colony Optimization (ACO), Genetic Algorithms (GA), Particle Swarm Optimization (PSO), Simulated Annealing (SA)) holds considerable promise [ 66 , 67 ]. Since the vacuum gate dielectric degrades the coupling capacitance, leading to worse carrier control, leveraging negative capacitance ferroelectric materials [ 68 , 69 , 70 ] to improve such carbon nanodevices can be a matter for further investigation. Furthermore, very interesting results are presented in [ 71 , 72 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…The design of ternary logic using CNTFET is more prolific than other well technologies due to the ease of adjusting the threshold voltage [54,55]. The CNTFET technology offers ballistic transport [56,57]…”
Section: Literature Survey On Cntfet-based Tsrammentioning
confidence: 99%
“…Among them, ferroelectric memristors consist of a ferroelectric film sandwiched between two electrodes. They offer advantages such as rapid reading and writing speeds, a continuously adjustable resistance state, a substantial switching ratio, and the absence of a need for an electroforming process. It is well-known that the occurrence of defects such as oxygen vacancies is unavoidable during the deposition of ferroelectric thin films. Therefore, many researchers have turned to the resistive switching (RS) effect of ferroelectric materials for drift and charge trapping in oxygen vacancy defects. Ferreyra et al revealed the significance of oxygen vacancy migration and polarization direction flipping in the RS and underscored the crucial role played by oxygen vacancies .…”
Section: Introductionmentioning
confidence: 99%